Analysis of business intelligence situation in Arequipa’s industrial sector - César Basilio Baluarte Araya (2019)
The research was conducted to gain an appreciation of the situation of business intelligence, also called business intelligence, at first in line to do research using a questionnaire to companies in the industry that leads us to understand reality with the firm intention to find and assess situations as a basis for formulating proposals or come to suggest alternative solutions to problems, this was achieved by having the conclusion that there must be a business intelligence model for this type of companies to act them in a very competitive market. This also could determine the areas of business interest and have a framework in training college students in the area of systems engineering in order to improve their learning and to graduate from their undergraduate education inclusion in the labor market is more preferred by the business requirements.